Peran Pengorganisasian Kementrian Agama dalam Meningkatkan Efektivitas Pemanfaatan Wakaf di Kota Bandung - Badruzaman, Defar; Aliyudin, Mukhlis; Herman, Herman (Tadbir: Jurnal Manajemen Dakwah, 2025)
Waqf has great potential to enhance societal well-being, yet its effectiveness faces challenges in organization, regulation, and management. This study analyzes the organizational efforts of the Ministry of Religious Affairs in Bandung City to optimize waqf, identifies obstacles and supporting factors, and evaluates the outcomes. Using a qualitative descriptive method, data were collected through interviews, document analysis, and observations. Findings indicate that waqf data digitization and nazhir training improve effectiveness, although understanding of productive waqf remains limited. Regulatory support and collaboration with the National Land Agency (BPN) are key success factors. This study contributes to sustainable waqf management strategies.